Pengembangan Bahan Ajar Teks Legenda yang Bermuatan Nilai Budaya Lokal Berbasis Pop-Up Book pada Siswa Kelas VII Madrasah Tsanawiyah Budi Agung Medan - Dhea Nabila Khairunisa; Rika Kartika; Rita Rita (Medan Resource Center, 2026)
This study aimed to develop, validate, and determine the effectiveness of Pop-Up Book-based legend text teaching materials integrating local cultural values for seventh-grade students at MTs Budi Agung Medan. The study employed the 4-D development model proposed by Thiagarajan, consisting of four stages: Define, Design, Develop, and Disseminate. The research involved all 34 seventh-grade students of MTs Budi Agung Medan as the sample. The developed teaching materials integrated local cultural values through regional folklore, moral messages, and local wisdom contained in legend texts. The results indicated that the product was feasible based on expert validation. Media Expert I and II rated the product 85% and 80%, respectively, while Material Expert I and II gave scores of 80% and 82%, respectively. The teacher evaluation resulted in a score of 87%, categorized as Very Feasible, and field testing with students obtained a score of 85%, also categorized as Very Feasible. Product effectiveness was measured through evaluation tests after implementation, and the results showed that the teaching materials met the Very Effective criterion. Therefore, the developed Pop-Up Book-based teaching materials are both feasible and effective for supporting legend text learning.